Killing the witches : the horror of Salem, Massachusetts [large type] - O'Reilly, Bill; Dugard, Martin (O'Reilly, Bill. Killing series., 2023)
"Killing the Witches revisits the events of 1692 and 1693 in Salem Village, Massachusetts. What began as a mysterious affliction of two young girls who suffered violent fits and exhibited strange behavior soon spread to other young women. Rumors of demonic possession and witchcraft consumed Salem. Soon three women were arrested under suspicion of being witches--but as the hysteria spread, more than two hundred people were accused. Thirty were found guilty, twenty were executed, and others died in jail or their lives were ruined. What really happened in Salem?"--